Determining factors that influence cancer screening rates in singapore - Lim, Jordan Andrew Wen Jiang (Nanyang Technological University, 2023)
With the rising number of cancer cases in Singapore, the importance of cancer screening should be further encouraged to ensure earlier detection and treatment of cancer. Hence, our study aims to shed light on factors that influence cancer screening rates in Singapore. Using information extracted from a sample of 3,023 Singaporean residents who had attended an appointment at the Cancer Genetics Service (CGS) of the National Cancer Centre Singapore (NCCS) between 2014 and 2020, we constructed logistic regression models to determine factors that may have an effect on cancer screening rate among individuals. Our results found that family history of cancer was not statistically significant on cancer screening rates. Individuals having 1 to 2 first-degree relatives (FDRs) affected by cancer was found to be statistically significant with a 26% increase in cancer screening rates relative to individuals without FDRs affected by cancer. However, results for 3 or more FDRs affected by cancer were found to be statistically insignificant. We have also found that the type of cancer contracted does have an effect on cancer screening rates, with breast, ovarian and endometrial, prostate, and blood cancer being statistically significant, while gastric, neuroendocrine, and other cancers were statistically insignificant. Further research could be done to determine the effectiveness of raising awareness of cancer screening through public health campaigns and advertising, as well as the effectiveness that government aid could have on cancer screening uptake. Additionally, further research could also be carried out in studying factors that contribute to the phenomena of fatalism in Singapore, and how they could affect cancer screening rates.